2015
DOI: 10.4103/0028-3886.158218
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification of vertebral artery vulnerability during surgery for congenital atlanto-axial dislocation with or without an occipitalized atlas

Abstract: A preoperative detailed risk assessment of anatomical variations in the size and course of VA at the CVJ significantly reduces chances of its iatrogenic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…There have been recent publications in the classification of VAs and CAAD with risk stratification. [ 12 13 ] One of these studies observed that VAs often have an unusual course in the presence of occipitalization of arch of atlas, either passing through the bony canal or lies beneath the arch of atlas. [ 12 ] The bony canal itself may be anterior, posterior, or through the lateral mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been recent publications in the classification of VAs and CAAD with risk stratification. [ 12 13 ] One of these studies observed that VAs often have an unusual course in the presence of occipitalization of arch of atlas, either passing through the bony canal or lies beneath the arch of atlas. [ 12 ] The bony canal itself may be anterior, posterior, or through the lateral mass.…”
Section: Discussionmentioning
confidence: 99%
“…The authors did not use distract the joints and avoided lateral mass screws in the presence of anomalous or unusual course of VA.[ 12 ] Another study stratifies the risk of VA in surgery for CAAD. [ 13 ] However, any classification of the course should be relevant surgically.…”
Section: Discussionmentioning
confidence: 99%